Assessing Inequities in Cervical Cancer Quality of Care and Survival Related to Ethnicity and Socioeconomic Factors. Issue 3 (July 2021) - Cantwell, Christopher J.; Moroney, Marisa R.; Sheeder, Jeanelle; Guntupalli, Saketh R.
Abstract : Objective: This study aimed to assess the effect that race and socioeconomic factors have on the provision of care to cervical cancer patients based on National Comprehensive Cancer Network (NCCN) recommended treatment guidelines. Materials and Methods: To do this, we completed a retrospective cohort study using the American College of Surgeon's Nation Cancer Database from 2004 to 2016. We identified all reported cases of cervical cancer in that period. Two cohorts were created using self-reported racial demographic data, Hispanic- and White, non-Hispanic–identified patients. Our primary outcome variables were adherence to NCCN-recommended treatment and 5-year overall survival. Adherence to NCCN-recommended treatment was determined by the provision of surgical and/or radiation and/or chemotherapy treatment based on the clinical stage at time of diagnosis and the presence or absence of lymphovascular space invasion. We used bivariate analyses to compare baseline characteristics between the 2 cohorts, multivariable logistic regression to identify independent predictors of 5-year survival, and Cox proportional hazards models to compute survival by group. Results: The difference in NCCN-adherent care between the 2 cohorts was found to be not statistically significant ( p = .880). A log rank (Mantel-Cox) χ 2 test showed that there was a statistically significant difference between the 2 groups in overall survival with the Hispanic-identified patients living longer ( p < .001). Our study is limited by the effect large databases confer on finding statistical significance. Conclusions: Hispanic-identified women with cervical cancer receive NCCN-compliant care and live longer than their White, non-Hispanic counterparts.